Psikoedukasi Protokol Kesehatan dalam Mencegah Penyebaran Covid-19 di Desa Banding Agung - Anggita, Anggita Nadia (LPPPM STAI Darul Hikmah Bangkalan, 2021)
“Psychoeducation is a process of providing psychological understanding or education to individuals or groups. Corona viruses are a family of viruses found in humans and animals. Most of the virus can infect humans and cause variety diseases start from common illnesses such as the flu, to more fatal diseases, such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). The purpose of this community dedication is to provide understanding and education about the importance of wearing masks, washing hands, and consuming healthy food, motivating the people to pay attention to health during this covid-19 pandemic. The method of exspressing deep in psychoeducation is carried out directly such as providing counseling, and also through intermediary print media banner installation. The target of this activity is the general public of Banding Agung Village. The results from this psychoeducation are that most residents are motivated to keep up health and taking vitamins and food that’s healthy and nutritious foods, and Increased insight and knowledge about the importance of Stay healthy on the central of the COVID-19 pandemic.”